1990
DOI: 10.3758/bf03210875
|View full text |Cite
|
Sign up to set email alerts
|

Differential use of distance and location information for spatial localization

Abstract: Five experiments are reported in which subjects judged the movement or spatial location of a visible object that underwent a combination of real and induced (illusory) motion. When subjects attempted to reproduce the distance that the object moved by moving their unseen hands, they were more affected by the illusion than when they pointed to the object's perceived final location. Furthermore, pointing to the final location was more affected by the illusion when the hand movement began from the same position as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(52 citation statements)
references
References 53 publications
7
44
1
Order By: Relevance
“…More specifically, they have shown that overestimating target velocity has effects on both motor and perceptual responses. Analogous findings have recently been demonstrated for several types of visual illusion under certain conditions (e.g., Abrams & Landgraf, 1990;Gentilucci, Chieffi, Daprati, Saetti, & Toni, 1996;Mack, Heuer, Villardi, & Chambers, 1985;Post & Welch, 1996). The interesting aspect ofthe present results is that the overestimation of target velocity occurred only because of the active process of generating pursuit responses during the adaptation period.…”
Section: Control Adaptation O Comparison Of Smooth Pursuit and Velocisupporting
confidence: 67%
“…More specifically, they have shown that overestimating target velocity has effects on both motor and perceptual responses. Analogous findings have recently been demonstrated for several types of visual illusion under certain conditions (e.g., Abrams & Landgraf, 1990;Gentilucci, Chieffi, Daprati, Saetti, & Toni, 1996;Mack, Heuer, Villardi, & Chambers, 1985;Post & Welch, 1996). The interesting aspect ofthe present results is that the overestimation of target velocity occurred only because of the active process of generating pursuit responses during the adaptation period.…”
Section: Control Adaptation O Comparison Of Smooth Pursuit and Velocisupporting
confidence: 67%
“…Strong support for this idea in the context of reaching and grasping has been provided in recent experiments by Bingham (2001) and by Crowell, Todd, & Bingham (2001). A similar idea has been proposed in connection with 2-D shapes viewed in a frontoparallel plane (Abrams & Landgraf, 1990;Gillam, 1998;Gillam & Chambers, 1985;Mack, Heuer, Villardi, & Chambers, 1985;MacLeod & Willen, 1995;Post & Welch, 1996). Hypothesis 2: Accurate Perception of Location and Anisotropy of Perceived Extent-According to this hypothesis, based in part on a model originally posed by Foley (1991) and subsequently revised by Foley, Ribeiro-Filho, and DaSilva (2001), a unified visual space exists in which perceived locations fully constrain the perceived extents.…”
Section: Four Hypothesesmentioning
confidence: 65%
“…Previous studies have found that goal-directed reaching can, in some circumstances, be influenced by perceptual illusions, indicating that the awareness of a stimulus might determine the behavior [15][16][17][18][19][20][21][22] . Figure 3b shows that this did not occur in the present experiment.…”
Section: Author Manuscriptmentioning
confidence: 99%